The Cultural Importance of Water from the Perspective of 16th Century Polish Medical Guides - Odrzywolska, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Water had a special cultural significance in human life. Water was a cheap and widely available resource for everyone. Water has fulfilled a wide variety of functions over the centuries. People even believed in the magical properties of water. The water also had a symbolic effect - it cleansed the body from sins. However, it was during this period in Western Europe that drinking water was considered harmful to health. In spite of this, in the 16th century the poorest peasants and monks who lived the harsh monastery life were drinking water in Poland, also the monarchs from the Jagiellonian dynasty, who were afraid of poison, drank water. However, the richer social strata drank beer or, more rarely, wine. It was believed that stagnant water (in reservoirs) was spreading epidemics. The authors of medical guides claimed that drinking such water could cause infertility, dysentery and other diseases. Only boiling the water was a way to improve its properties. To eliminate the smell they were adding garlic, salt, and vinegar, the Tartars brought from Asia the custom of adding so-called Tatar herb, later called calamus, and other herbs (eg. mint, sage) were also added to the water.

Woda od najdawniejszych czasów miała szczególne znaczenie kulturowe w życiu człowieka. Była tanim i dostępnym dla każdego dobrem. Przez wieki spełniała wiele funkcji. Ludzie wierzyli nawet w jej magiczne działanie. Miała też efekt symboliczny – oczyszczała ciało z grzechów. Jednak w omawianym okresie w zachodniej Europie zaczęto uważać, że picie wody jest szkodliwe dla zdrowia. Mimo takiej opinii w XVI w. wodę pitną w Polsce pili najbiedniejsi chłopi i mnisi żyjący w ciężkim rygorze klasztornym, ale też monarchowie z dynastii Jagiellonów, którzy obawiali się trucizny. Jednak bogatsze warstwy społeczne piły piwo lub rzadziej wino. Wierzono, że stojąca woda (w zbiornikach) rozprzestrzenia epidemie. Autorzy poradników medycznych twierdzili, że picie takiej wody może powodować bezpłodność, czerwonkę i inne choroby. Dopiero gotowanie wody było sposobem na poprawę jej właściwości. Aby wyeliminować nieprzyjemny zapach, dodawano czosnek, sól i ocet. Z Azji od Tatarów przybył zwyczaj dodawania tzw. zioła tatarskiego, zwanego później tatarakiem. Do wody dodawano również inne zioła (np. miętę, szałwię). Bardziej ceniona była woda płynąca („woda żywa”), gdyż uważano, że picie takiej wody jest zdrowsze.
Keywords: water; medical guides; history of medicine; woda; przewodniki medyczne; historia medycyny